Assessment of Secondary Traumatic Stress in Health Care Professionals Working in Tertiary Care Hospitals of Islamabad : Assessment of Secondary Traumatic Stress in Health Care Professionals - Chaudhry, Maryam; Sharif , Hina; Masaood Shah, Sidra; Javed, Sadaf; Mangrio, Sana (Pakistan Journal of Health Sciences, 2022)
Health care professionals are at a higher risk of developing secondary traumatic stress due to various factors related to the nature of their job. Objectives: To assess the level, severity & factors associated with secondary traumatic stress symptoms among health care professionals working with trauma victims in tertiary care hospitals of Islamabad. Methods: A cross-sectional study was carried out in which 170 healthcare professionals participated from both public and private tertiary care hospitals of Islamabad. Data were collected by using STS Scale, TIPI and demographics. Analyses was done using independent t-test, ANOVA and Pearson’s Correlation Coefficient. Results: The results showed, 94(55.3%) and 71(41.7 %) little and mild to moderate level of STS in healthcare professionals respectively. Female gender was significantly associated with STS (p = 0.01) along with MBBS graduates (p = 0.02) and junior doctors (p = 0.01) showed symptoms of STS. Those who were exposed to trauma multiple times had significant association STS. Emotionally stable personality trait of the healthcare professionals had an indirect relation with the development STS symptoms (r= -0.46). Conclusions: The results emphasized hospital administration to take measures in order to reduce stress level especially among female HCWs, junior doctors and those who had multiple exposure of trauma. If necessary steps are not taken, this stress may lead to worse mental health of this target population